1988
DOI: 10.1136/gut.29.11.1564
|View full text |Cite
|
Sign up to set email alerts
|

Low gluten diet in the treatment of adult coeliac disease: effect on jejunal morphology and serum anti-gluten antibodies.

Abstract: SUMMARY Treatment of patients with coeliac disease with a low gluten containing diet (LGD) remains controversial. We have studied jejunal morphology and antigluten (AG) antibody titres by ELISA in patients on a LGD of 2.5-5 g/day for three to 14 months (median six months) and compared results with patients on a strict gluten free diet (GFD) for six to 27 months (median 13 months). We found no significant difference in villous height or crypt depth (eight LGD v 10 GFD patients) or serum AG-IgA, -IgG, and -IgM t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 20 publications
(2 reference statements)
1
34
0
2
Order By: Relevance
“…assessment and this is supported by the ob servation that 7 poorly complying patients with improvement of jejunal lesions were IgA AGA-negative. These patients, however, admitted some lapses from their diet, and this is in keeping with the report that adult coeliac patients can tolerate small quantities of gluten without morphological change and without initiating a significant IgA AGA re sponse [17], Previous attempts by other workers [ 18] failed to predict the status of the jejunal mucosa using noninvasive laboratory crite ria and concluded that, although dietary as sessment correlated more accurately with je junal mucosal findings than any of the pa rameters they measured, intestinal biopsy re mained the best means of determining the positive effect of GFD. We do agree with this view but our data show that, in coeliacs being IgA AGA-positive when untreated, the persistence of these antibodies after GFD is always predictive of the persistence of severe jejunal lesions.…”
Section: Discussionsupporting
confidence: 59%
“…assessment and this is supported by the ob servation that 7 poorly complying patients with improvement of jejunal lesions were IgA AGA-negative. These patients, however, admitted some lapses from their diet, and this is in keeping with the report that adult coeliac patients can tolerate small quantities of gluten without morphological change and without initiating a significant IgA AGA re sponse [17], Previous attempts by other workers [ 18] failed to predict the status of the jejunal mucosa using noninvasive laboratory crite ria and concluded that, although dietary as sessment correlated more accurately with je junal mucosal findings than any of the pa rameters they measured, intestinal biopsy re mained the best means of determining the positive effect of GFD. We do agree with this view but our data show that, in coeliacs being IgA AGA-positive when untreated, the persistence of these antibodies after GFD is always predictive of the persistence of severe jejunal lesions.…”
Section: Discussionsupporting
confidence: 59%
“…At present, two methods have been widely used to achieve a conclusive diagnosis of persistent gluten intolerance: the dosage of serum levels of AGA (GRECO et al, 1987;MAYER et al, 1989;VALLETTA et al,1990;BURGIN-WOLFF et al, 1991), and the observation of small intestinal biopsies by conventional histology (JUTo et al, 1985;KHosoo et al, 1988;MONTGOMERY et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that a 4-wk challenge with 100 mg gliadin/d caused deterioration of the small-intestinal architecture and that the histologic changes were more pronounced in patients challenged with 500 mg gliadin/d (2). Finally, a higher gluten intake (1-5 g/d), still lower than the normal gluten intake for the non-CD population in Western countries (10 -20 g/d) (24), caused relapse of disease at a clinical, laboratory, and histologic level, both in children and in adults (25)(26)(27). On the basis of the evidence from the current study and the quoted literature, it appears that 50 mg gluten/d is the minimum dose required to produce measurable damage to the small-intestinal mucosa in CD patients.…”
Section: Discussionmentioning
confidence: 99%